A Meta-Analysis of Attitudes toward Doping among Korean Athletes - Jonghwa Lee; Soojin Kang; Dojin An; Youngho Kim (Asian Society of Kinesiology, 2024)
OBJECTIVES The purpose of the current study was to conduct a meta-analysis to comprehensively analyze and identify research on doping attitudes studied in Korea. METHODS Twelve articles were selected for analysis by searching for 'doping attitudes' and 'doping PEAS' in Korean academic databases. The meta-analysis was conducted using the meta-analysis package in the R program (ver.4.3.2). RESULTS Results indicated that 12 literatures on Korean athletes' doping attitudes revealed an average PEAS mean score of 37.20 (95% CI = 34.29, 40.11). Moreover, results found that 10 articles on gender differences in Korean athletes' doping attitudes showed a small effect size of -0.23 (95% CI = -0.34, -0.12), and a significant difference (p < .0001), with that female had higher mean PEAS scores than males. Results indicated that 4 studies on the difference in doping attitudes based on doping experience were found to have publication bias, so we meta-analyzed two additional studies using a trim-and-fill algorithm and found a moderate effect size of -0.64 (95% CI = -1.23, -0.05), with a significant difference (p = .0343). Additionally, Korean athletes with doping experience had higher mean PEAS scores than those without doping experience. CONCLUSIONS This study suggests that attitudes may be important in predicting doping intentions or doping behavior.